Seasonal and spatial variability of nematodes and macrofauna assemblages in the Mondego estuary: can these communities provide comparable ecological assessment information? - Alves, Ana (2012)
With the implementation of the European Water Framework Directive there is the need to develop assessment tools based on biological data, which are adequate for all European aquatic systems. Macrofauna communities have traditionally been used to assess and evaluate ecological integrity. However, meiofauna communities can also suitably reflect the ecological conditions present in a particular system. Free-living nematodes are the dominant fraction of meiofauna communities. Their importance in the nutrients cycle is known and their use as biological indicators has been registered worldwide. Nevertheless, the outputs given by the study of nematodes communities in the assessment of quality in estuarine systems are poor, compared with those given by macrobenthic assemblages. The main objective of this study was to examine spatial and temporal variations of density and diversity of nematodes and macrofauna communities and to understand how diversity indices were influenced by season and by “target” community. The questions addressed in this study were 1) which environmental variables were the most important in influencing the distribution of the communities? and 2) did free-living nematodes and macrofauna assemblages provide comparable ecological assessment information? Differences between the ecological conditions were detected considering both communities, with nematodes assemblages presenting a higher quality status. Besides spatial variations, seasonal differences were also recorded for both communities. Probably, these seasonal changes could be related with recruitment events and other population processes, which in turn affected the diversity indices. Future research should focus on defining the best sampling period and exploring the reasons behind different ecological assessments provided by both communities (e.g. distinct response times).